2020
DOI: 10.1002/csc2.20150
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and physiological performance of an indicajaponica rice variety with a high yield and high nitrogen use efficiency

Abstract: Hybrid rice (Oryza sativa L.) varieties usually need more N application to produce a higher grain yield and exhibit lower N use efficiency (NUE) than inbreds. However, little information is available about the mechanism underlying an indica-japonica rice variety with high yield and high NUE under low N rates. This study investigated this issue. The indica-japonica hybrid rice variety Yongyou 2640 (Y-2640) and the japonica inbred rice variety Lianjing 7 (L-7) were grown in a paddy field at N rates of 0 and 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Other studies have shown that improvements in the agronomic and physiological traits of rice contribute to yield enhancement (Cao et al., 2017; Chu et al., 2019; Li et al., 2012; Zhang et al., 2018; Zhu et al., 2020). In our study, two N treatments significantly increased plant height, LAI, LAD, aboveground biomass, RDW, number of panicles and spikelets per panicle of two rice genotype plants as compared with 0N treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that improvements in the agronomic and physiological traits of rice contribute to yield enhancement (Cao et al., 2017; Chu et al., 2019; Li et al., 2012; Zhang et al., 2018; Zhu et al., 2020). In our study, two N treatments significantly increased plant height, LAI, LAD, aboveground biomass, RDW, number of panicles and spikelets per panicle of two rice genotype plants as compared with 0N treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LHT1 expression is observed mostly in source organs and is likely involved in the transport of amino acids between mesophyll cells and the xylem ( Ehness and Roitsch, 1997 ; Hirner et al, 2006 ). Experiments outside of the model plant species Arabidopsis have also provided evidence of the association between cytokinins and regulation of the expression of genes involved in amino acid transport ( Song et al, 2015 ; Ninan et al, 2019 ; Zhu et al, 2020 ). In addition to these observed changes in expression of amino acid transporter genes in response to cytokinins, corresponding changes in amino acid translocation are also observed.…”
Section: Cytokinin Regulation Of Source-sink Relationships: Effect On Amino Acid Transportmentioning
confidence: 99%
“…These cultivars produce significantly improved yields on account of the larger panicles and longer growth season compared with typical indica hybrid rice 15 , 16 . The nitrogen fertilizer application rate is important for dry matter accumulation, a high application rate is necessary in indica–japonica hybrid rice to obtain a higher yield than that attained with inbred hybrid rice 17 , 18 . In particular, nitrogen application must be sufficient to meet the demand for spikelet differentiation and the longer grain-ripening period 19 .…”
Section: Introductionmentioning
confidence: 99%